Nuclear DNA Content and Chromatin Pattern of Rat Rhabdomyosarcoma Cell Sublines with Different Metastatic Potentials - Jean Dufer; Marie-France Poupon; Sonia Yatouji (Analytical Cellular Pathology)
There is a constant need of features able to characterize potentially metastatic cells among the heterogeneous cell subpopulations which constitute a tumor. Image cytometry of metastatic tumor cells give rise to variable results, partly because of a heterogeneous origin of cells, or potential drug effects. The aim of this work was to characterize nuclear changes observed in metastatic cell clones issued in vitro from the same parental cell population The nuclear phenotypes of 6 cell sublines isolated from a rat rhabdomyosarcoma cell line and differing in their metastatic ability were evaluated by image cytometry on Feulgen‐stained preparations. Densitometric [5], geometric [3] and textural [9] features were computed from each nuclear image. For each cell subline, a metastatic score, ranging from 0 to 10, was calculated on the basis of in vitro invasivity data, by measuring the number of pulmonary metastases observed after s.c. graft of tumor cells in rats. Data obtained were compared to karyotype, growth characteristics, and oncogene expressions of cell lines. The nuclear DNA content, the chromosome numbers, the cell sublines doubling times, and the distribution of cells within the cell cycle appear unrelated with this score. On the contrary, increase in metastatic ability is accompanied by changes in chromatin pattern as assessed by textural features. Progressive increase in chromatin condensation can be observed in cell sublines with increasing metastatic score. These results were confirmed by an unsupervised multivariate partitioning of rhabdomyosarcoma cells which identified two separate subsets whose distributions within the analyzed cell lines correlate with their metastatic ability. These data suggest that, in rat rhabdomyosarcoma cell sublines, metastatic ability could be associated with nuclear morphological changes at the level of chromatin texture.